Host–parasite interaction: an insight into the growth and physiological responses of sandalwood and associated host species - Verma, Kamlesh; Kumar, Ashwani; Kumar, Raj; Bhardwaj, Ajay Kumar; Devi, Sunita; Sharma, Aarju; Sharma, Prashant (Frontiers in Forests and Global Change, 2024)
Introduction Sandalwood (Santalum album L.) is categorized as vulnerable in the IUCN Red list and is also an industrially important tree species valued for its heartwood and aromatic oil. Sandalwood is a semi-root parasite tree that relies on its host plants for its water and nutrient requirements. Therefore, there is need to understand the growth and physiological interactions between sandalwood and its hosts. Methods Sandalwood were planted with ten different host species viz., Syzygium cumini, Punica granatum, Phyllanthus emblica, Melia dubia, Leucaena leucocephala, Dalbergia sissoo, Casuarina equisetifolia, Citrus aurantium, Azadirachta indica and Acacia ampliceps to assess the interactive effect on the change in growth and physiology of both sandalwood and host tree species. Results The findings revealed that sandalwood grown with hosts D. sissoo and C. equisetifolia showed higher growth performance, while among hosts, S. cumini, followed by C. aurantium and L. leucocephala, showed better growth and physiobiochemical traits. The stepwise regression analysis and trait modeling indicated that the six traits, namely, plant height, photosynthetic rate, relative water content, water potential, intercellular CO2 concentration, and total soluble protein, contributed greater growth in the sandalwood, while four traits, namely, water potential, osmotic potential, leaf area, and total soluble protein, contributed greater growth in the host species. The traits modeling study predicted greater growth of sandalwood with the hosts D. sissoo and C. equisetifolia, whereas among host species, prediction revealed greater growth of S. cumini and C. aurantium. Discussion The study concluded that host–parasite interaction modulated the growth and physiological processes in both sandalwood and hosts and sandalwood plantations can be successfully developed with the hosts D. sissoo and C. equisetifolia.